PENGARUH LEVERAGE, UKURAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS - Sunarto, Sunarto; Budi, Agus Prasetyo (Jurnal Ilmiah Telaah Manajemen, 2009)
This research is conducted as a mean to test influence of leverage, company size and growth to profitability of Distric Drinking Water Company (PDAM) in Central Java Province during period 2004- 2007. Research sample taken on sampling purposive basis. Criterion of Sample fulfilling counted 21 companies. Analysis technique using multiple regression with of ordinary square least (OLS) technique. Amount of sampel fulfilling normalitas counted 81 was later on used for analysiseses. Result of analysis prove that by simultan variable of leverage, company size and growth of company have an effect on profitability of PDAM which in Central Java Province. This Result is shown with F sig 0,000 or at level less than 0,05. while by parsial, two independent variable the having an effect on is variable of leverage company size and posed at with signifikansi equal to 0,014 and 0,000 while variable growth of company do not have an effect on to profitability of PDAM.Keyword : Leverage, Company Size, Company, Growth , and Profitability